iKids study protocol: a longitudinal study to understand the impact of interactive electronic devices on the development and health of young children in England - Jenny Retzler; Daniel Jones; John J Reilly; John Stephenson; Stuart Fairclough; Christine Smith; Amy Hughes; Tony Okely; Liane Beretta De Azevedo; João Paulo de Aguiar Greca; Colette Marr (BMJ Open)
Introduction There is evidence of both positive and negative impacts of interactive electronic devices (IEDs), such as tablets and smartphones, on young children’s development and health outcomes. Consultations with early years practitioners, parents and policy makers recognise IEDs as a valuable resource for early-year learning. However, concerns exist regarding their potential negative impacts on children’s self-regulation, parent-child interaction and physical activity.The primary aim of this study is to understand the longitudinal impact of IED use, in particular duration (hours per day) and mode (educational vs non-educational; age-appropriate vs non-age-appropriate), on emerging abilities (ie, self-regulation, social development, executive function, language and numeracy) in 3-year-old to 5-year-old children. The secondary aims are to explore the impact of IEDs on health-related outcomes (ie, body mass index and motor skills), behavioural outcomes (ie, movement behaviour, parent-child interaction) and educational outcomes (ie, school readiness).Methods and analysis We aim to recruit 1377 children from economically diverse areas in the Mid and North of England, UK. We will measure children’s exposure to IEDs using a mobile sensing application tool which records app usage, while the primary outcome, emerging abilities, will be measured through the Early Years Toolbox. The secondary outcome measures will include the following: accelerometry (24-hour movement behaviour), National Institute of Health (NIH) Toolbox (motor skills), STIM-Q preschool questionnaire (parent-child interaction) and early years foundation stage profile (school readiness). We will employ multilevel regression models to examine the association between IED duration and mode with emerging abilities. We hope this study will contribute to the development of guidelines for parents and educators regarding the use of IEDs.Ethics and dissemination The study has received approval from Sheffield Hallam University (ID: ER69550320). Engagement with the public and stakeholders will guide the dissemination plan. The insights gained from this project will be shared through publications and will inform policy briefs distributed to health and educational organisations.Trial registration number NCT06810570.